2009
DOI: 10.1111/j.1743-7563.2009.01229.x
|View full text |Cite
|
Sign up to set email alerts
|

Reversible encephalopathy following 5‐fluorouracil‐based chemotherapy in patients with dihydropyrimidine dehyrogenase deficiency

Abstract: 5-fluorouracil (5-FU) is one of the most frequently used chemotherapy agents for the treatment of a number of solid cancers. We report two patients with advanced gastric cancer who developed acute encephalopathy after receiving chemotherapy composed of 5-FU and oxaliplatin. One patient presented with altered consciousness and the other with generalized tonic clonic seizure. 5-FU-induced encephalopathy was suspected by clinical, radiological and electroencephalographic findings, and both patients had reduced ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…The pathophysiology linking fluoropyrimidines and encephalopathy has not been well described but at least three pathogenic explanations have been suggested. The first theory proposes that a deficiency in dihydropyrimidine dehydrogenase (DPD), the initial and rate‐limiting enzyme in the catabolism of fluoropyrimidines, is associated with more severe and generalized forms of 5‐FU toxicity 27,28 . A deficiency in DPD results in the decreased metabolism of 5‐FU and the accumulation of toxic compounds.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The pathophysiology linking fluoropyrimidines and encephalopathy has not been well described but at least three pathogenic explanations have been suggested. The first theory proposes that a deficiency in dihydropyrimidine dehydrogenase (DPD), the initial and rate‐limiting enzyme in the catabolism of fluoropyrimidines, is associated with more severe and generalized forms of 5‐FU toxicity 27,28 . A deficiency in DPD results in the decreased metabolism of 5‐FU and the accumulation of toxic compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Retrospective studies have suggested that up to 50% of 5‐FU toxicities maybe due to a DPD deficiency 29 . In one report, two patients developed an acute encephalopathy after receiving 5‐FU and oxaliplatin and on testing with quantitative real‐time polymerase chain reaction, both patients were shown to have reduced expression of DPD 28 . The second theory, proposed by Koenig and Patel, suggests that the neurotoxicity maybe due to the blockade of the Krebs cycle by fluoroacetate, a product of fluorouracil catabolism 30 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Platinum salts are a well-known trigger of AVP hypersecretion (6), and they have a direct toxic effect on endothelial cells (26,27). 5-Fluorouracil can cause a direct neurotoxic effect through the interruption of Krebs cycle or through thiamine deficiency (28,29); a neurotoxic effect is reported also in case of dihydropyrimidine dehydrogenase (DPD), the initial and ratelimiting enzyme in the catabolism of fluoropyrimidines (30,31).…”
Section: Chemotherapy and Pres: What Does Our Case Add To The Literatmentioning
confidence: 99%
“…Reversible Posterior Leukoencephalopathy syndrome (RPLS) has been first reported by Hinchey et al It is a rare neurologicoradiologic syndrome that is characterized by headache, altered alertness and behavior ranging from drowsiness to stupor, seizures and visual loss (1). Magnetic resonance imaging (MRI) reveals characteristic hyperintense lesions on T2-or FLAIR-weighted imaging and restricted diffusion with low ADC involving the posterior circulation areas (2)(3)(4). Recently, some cases have been reported in association with the increased use of cytotoxic and molecular target agents in cancer patients (5,6).…”
Section: Reversible Posterior Leukoencephalopathy Syndrome After Eribmentioning
confidence: 99%